ANALISIS HUKUM TERHADAP GUGATAN PERBUATAN MELAWAN HUKUM DAN WANPRESTASI DALAM PUTUSAN NOMOR 460/Pdt.G/2022/PN Sgr: TANGGUNG JAWAB KOPERASI DALAM PERJANJIAN DEPOSITO BERJANGKA - wahyuni, dini; Idaul Hasanah; Djoko Tritjahjana (Program Studi Hukum Keluarga Islam, 2025)
Abstract This study examines the breach of contract in a term deposit agreement. The main focus of this study is to understand the legal considerations taken by the judge in granting the exception filed by the Defendant, which resulted in the rejection of the Plaintiff's lawsuit due to formal defects, as well as the implications of this decision on the counterclaim and the main case. The results of the study indicate that the combination of the Unlawful Act (PMH) and breach of contract lawsuits in one lawsuit can cause ambiguity (obscuur libel), which in turn results in the lawsuit being declared inadmissible (niet ontvankelijk verklaard). In addition, this decision also provides an opportunity for the Plaintiff to file a new lawsuit after correcting the existing formal deficiencies. This study emphasizes the importance of separating the two types of lawsuits in order to maintain legal clarity and certainty in the judicial process. In addition, it is recommended that legal practitioners be more careful in drafting lawsuits so as not to lose the right to obtain justice. Keywords: Unlawful Acts; Breach of Contract; Cooperatives.